Heat Shock Protein-Mediated Resistance to High Hydrostatic Pressure in Escherichia coli - Aertsen, Abram (American Society for Microbiology, 2004)
A random library of Escherichia coli MG1655 genomic fragments fused to a promoterless green fluorescent protein (GFP) gene was constructed and screened by differential fluorescence induction for promoters that are induced after exposure to a sublethal high hydrostatic pressure stress. This screening yielded three promoters of genes belonging to the heat shock regulon (dnaK, lon, clpPX), suggesting a role for heat shock proteins in protection against, and/or repair of, damage caused by high pressure. Several further observations provide additional support for this hypothesis: (i) the expression of rpoH, encoding the heat shock-specific sigma factor σ(32), was also induced by high pressure; (ii) heat shock rendered E. coli significantly more resistant to subsequent high-pressure inactivation, and this heat shock-induced pressure resistance followed the same time course as the induction of heat shock genes; (iii) basal expression levels of GFP from heat shock promoters, and expression of several heat shock proteins as determined by two-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis of proteins extracted from pulse-labeled cells, was increased in three previously isolated pressure-resistant mutants of E. coli compared to wild-type levels.